2009
DOI: 10.1063/1.3180816
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of H atom production in hot filament activated H2 and CH4/H2 gas mixtures

Abstract: This article reports systematic measurements of the power utilization by Ta (and Re) hot filaments (HFs) operating in a poor vacuum, in pure He, N(2), and H(2), and in CH(4)/H(2) gas mixtures of relevance to diamond growth by HF chemical vapor deposition, as functions of filament temperature T(fil) (in the range of 1800-2700 K) and gas pressure p (in the range of 10(-2)-100 Torr). In the cases of H(2) and the CH(4)/H(2) gas mixtures, the power consumption studies are complemented by in situ measurements of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…If a filament is used, it must be held in close proximity to the substrate and maintained at a temperature >2000°C, whereupon surface-catalysed hydrogen decomposition yields H atoms. 34 The most common filament materials are W, Ta, or Re because of their high melting points. Laser and mass spectroscopic measurements of key species (including H atoms, [35][36][37][38][39][40] and CH3 radicals 37,41,42 ) in HF-activated CH4/H2 gas mixtures, coupled with thermodynamic and gas-kinetic modelling, 27,43 have yielded a fairly complete picture of the prevailing gas-phase chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…If a filament is used, it must be held in close proximity to the substrate and maintained at a temperature >2000°C, whereupon surface-catalysed hydrogen decomposition yields H atoms. 34 The most common filament materials are W, Ta, or Re because of their high melting points. Laser and mass spectroscopic measurements of key species (including H atoms, [35][36][37][38][39][40] and CH3 radicals 37,41,42 ) in HF-activated CH4/H2 gas mixtures, coupled with thermodynamic and gas-kinetic modelling, 27,43 have yielded a fairly complete picture of the prevailing gas-phase chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify this loss, He was used instead of H 2 , because with the latter the heat transport effects due to the gas flow and atomic hydrogen recombination cannot be separated. This procedure is similar to that reported earlier [32][33][34][35]39 where the H 2 cracking experiments were conducted first with He to measure the convective cooling of the filament due to the flowing gas. Next, the measured effect was adapted to H 2 to account for the differences between the two gases.…”
Section: Heat Losses By Convection In the Gasmentioning
confidence: 76%
“…The flux increases exponentially with the filament temperature, which is in agreement with the previous findings regarding H 2 cracking and recombination studies. 31,39,44 Such exponential dependence on filament temperature can be explained by the H 2 dissociation at the hot filament surface being a thermally activated process. 34,35,44,45 A promising result in view of application of atomic hydrogen for cleaning surfaces (e.g., optics) is that the radical flux increases proportionally with the H 2 flow rate through the gun.…”
Section: B Quantification Of the Atomic Hydrogen Fluxmentioning
confidence: 99%
“…Their assumption of the thermal decomposition of H 2 in the gas phase is in contradiction to the results of more recent studies. 5,6,[19][20][21] It has been shown that the catalytic decomposition on wire surfaces is the dominant source of H atoms and gas-phase reactions play only a negligible role.…”
Section: Resultsmentioning
confidence: 99%